Product functions: interfaces with ergonomic design - Campos, Livia F. de A. [UNESP]; Lanutti, Jamille N. de L. [UNESP]; Paschoarelli, Luis Carlos [UNESP] (IOS Press, 2012)
In addition to technical quality, increasing emphasis is being placed on the importance of elements such as the appearance and meaning of products. To be successful, therefore, attention must be paid to the aesthetic and symbolic functions of objects as well as to reliability and physical quality. Study of the interfaces of these functions may provide a theoretical basis for the ergonomic design of products. The objective of this review is to attempt to establish the nature of these interfaces.
Keywords: ergonomic design; emotion; practical function; aesthetic function; symbolic function